Legal aspects of functional security standardisation of the Internet of Things (Law and Safety, 2023)
IoT technologies provide smart things with the ability to make decisions in the management of physical objects using intelligence and consensus. To support the Internet of Things, technologies such as built-in devices, cloud and fog computing, big data processing, machine learning, and artificial intelligence are used to produce intelligent physical objects. A review of existing security infrastructures for IoT-based intelligent environments shows that every connected device can be a potential entry point for an attack.An overview of the key aspects of security standards for smart environments based on the Internet of Things has been provided in the following areas: potential solutions, intelligent environments, limits of security assessment, open issues and challenges. Additional research on the development of methodological and technological standardisation measures in the field of interoperability of heterogeneous IoT devices is an urgent task in order to start further discussions on the development of new security standards and certification infrastructure for smart environments based on the IoT.Based on the analysis of the existing problems of implementing the Internet of Things, the methodological and technological features of legal regulation of intellectual environments have been studied. The structures of standardisation of networks and services of the IoT environments at the regional, European and global international levels have been considered.The architecture of the Internet of Things environments has been defined as a multi-level, heterogeneous system with a complex topology and the use of innovative technologies. The single phenomenon of IoT security has been identified as a complex concept that includes functional security and information security with their interconnection, contradictions, challenges and risks.The functional security of the Internet of Things has been studied in terms of the security function, security completeness and resilience, which are subject to regulation in the technical requirements for the product being designed. An aspect model of IoT interoperability has been presented and examples of its application in terms of interrelated components (transport, syntactic, semantic, behavioural, and policy aspects) have been given.An assessment of generally accepted practices and risks of creating regulatory documents (standards, instructions, methodological materials) in the field of functional security of the Internet of Things has been carried out. Recommendations for the introduction of a scientifically based approach to national standardisation of IoT security and measures to address the problem of interoperability of heterogeneous IoT devices have been provided.
Keywords: Internet of Things (IoT); security standards; security certificates; functional security; information security; interoperability.